Die morfologie van die saadknop van Suid-Afrikaanse Proteaceae - Jordaan, P. G.(Pieter Gerhardus),1913- (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (D. Sc.) -- Universiteit van Stellenbosch, 1944.